Real-Time Visualization of Disaster Behavior - Estuar, Ma. Regina Justina E (Archīum Ateneo, 2014)
This paper presents the design principles and the technologies being used in the ongoing development of eBayanihan Patroller, a crowd-sourcing application for disaster risk reduction and mitigation. We show in this paper how we applied design principles in the creation of screens and icons as well as actual visualization on the map for a mobile-web based disaster management system reports. Specifically, we exercised abstraction of data processing through the MVC architecture to focus on visualization. We used a partial view to isolate the map configuration. Development of a visualization module using this framework provided not only convenience in development but also made distribution of tasks more efficient.